2022
DOI: 10.1111/1753-6405.13222
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate in drinking water and cancer risk: the biological mechanism, epidemiological evidence and future research

Abstract: also proliferate in the gastrointestinal tract (stomach, small intestine and large intestine). 16,17 Thus, nitrite, nitric oxide and other nitrosation agents are potentially bioavailable throughout the gastrointestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In the list of carcinogens published by the International Agency for Research on Cancer of the World Health Organization, nitrite is classified as a class 2A carcinogen, posing a potential threat to human health . The results in Figure A show that all samples possess higher NIAC at pH 2.0 than at pH 7.0, implying that the adsorption of NO 2– by IDF occurs mainly in the stomach.…”
Section: Resultsmentioning
confidence: 98%
“…In the list of carcinogens published by the International Agency for Research on Cancer of the World Health Organization, nitrite is classified as a class 2A carcinogen, posing a potential threat to human health . The results in Figure A show that all samples possess higher NIAC at pH 2.0 than at pH 7.0, implying that the adsorption of NO 2– by IDF occurs mainly in the stomach.…”
Section: Resultsmentioning
confidence: 98%
“…One of the public health concerns in short-term exposure, methemoglobinaemia is the most common health effect on babies. In addition, researchers found that there was a risk of childhood central nervous system, stomach, brain and colon cancers, glioma and birth defects [ 55 , 56 ]. Nitrate speeds up the production of chloropicrin which is a disinfection byproduct responsible for mutagenesis in bacterial experiment; however some of the hazards of nitrate as a cause of cancer remain controversial [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the MAV for nitrate is 11.3mg/L nitrate nitrogen, but emerging evidence suggests increased risks of bowel cancer 12 and pre-term births 13 at 0.87 mg/L and 5mg/L, respectively (albeit these relationships still involve some uncertainty and have not yet been proven to be causal). 14 The current water service delivery is also contributing to health inequities. Over the 2009-2016 period, supplies serving fewer than 5,000 people accounted for virtually all (96%) of test samples with unacceptable levels of contamination by bacteria.…”
Section: Problems With the Current Water Management Systemmentioning
confidence: 99%